2015
DOI: 10.1242/jcs.174771
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dendrite growth and maintenance by exocytosis

Abstract: Dendrites lengthen by several orders of magnitude during neuronal development, but how membrane is allocated in dendrites to facilitate this growth remains unclear. Here, we report that Ras opposite (Rop), the Drosophila ortholog of the key exocytosis regulator Munc18-1 (also known as STXBP1), is an essential factor mediating dendrite growth. Neurons with depleted Rop function exhibit reduced terminal dendrite outgrowth followed by primary dendrite degeneration, suggestive of differential requirements for exoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 78 publications
3
32
0
1
Order By: Relevance
“…S2 cells were cotransfected with Myc-Sec71 and different forms of (data not shown). Consistent with our observations, a previous study also reported Sec15 distribution in larval sensory neurons (Peng et al, 2015). Some Sec15-positive puncta were localized adjacent to or partially colocalized with the Arf1-positive Golgi apparatus (Fig.…”
Section: Sec71 Is An Arf1gef That Preferentially Interacts With Gdpbosupporting
confidence: 92%
“…S2 cells were cotransfected with Myc-Sec71 and different forms of (data not shown). Consistent with our observations, a previous study also reported Sec15 distribution in larval sensory neurons (Peng et al, 2015). Some Sec15-positive puncta were localized adjacent to or partially colocalized with the Arf1-positive Golgi apparatus (Fig.…”
Section: Sec71 Is An Arf1gef That Preferentially Interacts With Gdpbosupporting
confidence: 92%
“…Indeed, a number of neuronal intrinsic factors have been identified that specifically regulate spacefilling of neurons. These factors include transcription factors that collectively determine the neuronal identity and bestow upon neurons the capacity to elaborate exuberant neurites (7,8), motor proteins and components of the secretary pathway that control the number and position of high-order dendrites (9)(10)(11)(12), and an amino acid transporter that allows neurons to grow total dendritic length beyond a certain threshold (13). In contrast to intrinsic control of dendritic growth, extracellular regulation of space-filling is more mysterious.…”
mentioning
confidence: 99%
“…The SIP is widely used to analyze differences and changes in dendritic morphologies (see, for example, Rekha et al, 2011;Williams et al, 2013;Peng et al, 2015;Johnson et al, 2016;Chittajallu et al, 2017;Keil et al, 2017). We have shown previously that the SIP can be accurately predicted from three factors with more functional interpretations: the dendrite spanning field, the centripetal bias, and the total length.…”
Section: Interpreting Changes In Sipmentioning
confidence: 99%
“…Fractal measures of neuronal morphology (Smith et al, 1989;Caserta et al, 1990), which quantify how well a dendrite fills its space, have also been shown to correlate strongly with statistics derived from the SIP (Caserta et al, 1995;Ferná ndez and Jelinek, 2001). Most recently, SIPs have been widely used to demonstrate changes in neuronal structure caused by genetic manipulation (O'Keeffe et al, 2008;Peng et al, 2015), pathology (Williams et al, 2013;Chittajallu et al, 2017), or treatment (Kigerl et al, 2009;Rekha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%